KETERLIBATAN AYAH DALAM PENGAMBILAN KEPUTUSAN RASIONAL UNTUK MENIKAH MELALUI PROSES TA’ARUF - ANNA ARMEINI RANGKUTI; DIANDRA ARIANI SYAFITRI (Journal of Research and Measurement in Psychology, 2017)
This study aims to determine the influencer of fathers involvement on rational decision making. This study is a quantitative research with sample of early adult women amount 101 respondents. The method of data collection is using Rational Decision Making, Nurturant Fathering Scale, and Reported Father Involvement Scale questionnaires that has been constructed by the relevant theory. Hypothesis testing in this study is using regression analysis. Regression analysis shows that the value of F count = 4,894 > F tabel = 3,94. Additionally significant value show that p = 0,029 < α = 0,05. The regression equation generated in this study is positive, which means that higher fathers involvement then makes rational decision making higher too. Besides, this reseaech R square of 0,047, which explains the influence of fathers involvement against rational decision making amount 47%. Based on the calculation of data shows that there is a significant influence of fathers involvement against rational decision making.